Sistem Monitoring Temperatur Mesin Dies Molding - Purnomo, Bayu; Riski Hidayat, Riski (University of Muhammadiyah Tangerang, 2024)
PT. Yasunli Abadi Utama Plastik is a company operating in the manufacturing sector that produces motor vehicle body products. Using the Root Cause Analysis (RCA) research method, a problem was found in one of the production processes in injection molding, the plastic injection section with the product COVER R FR IDE K1Z where there was no reference to the actual temperature of the mold so that operators often started the production process before molding. reaches standard temperature according to work instructions, which causes production defects in the form of NG Silver. NG Silver is a product defect caused by bubbles trapped in the product forming cone lines. This problem will disrupt the daily production planning that has been determined and has the potential to increase production costs due to overtime work by employees to achieve production targets. The solution to this problem Shaking Water Bath Temperature and speed control have been made with using heater 1500 W, 220 V and termocouple sensor type K. This heater use a receiver (keypad) for controlling and viewing the valve of rotation speed (rpm) and temperature (˚C) by set in set point (SP). Way of rotation speed regulation is with controll the width of pulse (PWM). With maximum power, will have the temperature only 98˚C with maximum speed 600 rpm..